Dampak Pembatasan Kegiatan Masyarakat Terhadap Pertumbuhan Ekonomi: Suatu Kajian - Mohammad Orinaldi (J-MAS (Jurnal Manajemen dan Sains), 2021)
This study aims to review various policies taken by the government when the government considers priorities balance between handling Covid-19, namely by implementing restrictions on community activities and the country's economic conditions. This research is a type of qualitative research with descriptive method. Descriptive method was chosen because the research was conducted with current events related to current conditions. The results of this study indicate that Indonesia has not implemented significant policies while still implementing normal human inflows from abroad. Either, a new policies’s the end of PSBB and changes to the Implementation of Community Activity Restrictions (PPKM) which was launched by the Chair of KPCPEN on January 7, 2021 with the first locus in Java and Bali. Observing the economic crisis history that hit Indonesia, many parties will be grateful, considering that the impact of the Covid-19 pandemic on the economy was no more severe than the monetary crisis in 1998. Currently, the government has adopted six strategies for Indonesia's economic transformation: (1) Competitive Human Resources; (2) Economic Sector Productivity includes Industrialization, (3) Green Economy includes a low carbon economy, blue economy, and energy transition aimed at meeting increasing energy needs, opening up more sustainable green job opportunities, and supporting the reduction of greenhouse gas emissions; (4) Digital Transformation; (5) Domestic economic integration; and (6) Relocating the National Capital as a new source of growth and balancing the economy between regions